The role of myokines in obesity-related osteoarthritis: linking physical activity to joint health - Pysiewicz, Mateusz; Budzik, Paweł; Stadnicka, Olga; Malaya, Elizabeth; Mokrzecki, Szymon; Wolnik, Julia Elżbieta; Grzywacz, Martyna (Quality in Sport, 2026)
Background: Osteoarthritis is a chronic, degenerative joint disease, which manifests mainly with joint pain, but with disease progression may also lead to much lower quality of life and disability. Its progression is associated with obesity and a sedentary lifestyle, while physical activity seems to be a protective factor. Studies in murine models suggest a potential role for myokines – molecules secreted by skeletal muscle during contraction. They appear to have anti-inflammatory effects and may improve joint health. Aim: The aim of this review was to evaluate the role of myokines as potential mediators linking obesity, physical activity and osteoarthritis progression. Additionally, we aimed to summarise current evidence on the impact of obesity and weight loss on osteoarthritis and to assess the immunomodulatory functions of selected myokines, particularly irisin and IL-6. Materials and methods: This paper is a narrative review. A literature search was conducted in the PubMed database up to February 2026. For part 2., the following terms were used: “osteoarthritis” combined with “obesity” with a preference for meta-analyses and large cohort studies. For part 3., the following terms were used: “myokines”, “irisin”, “IL-6” alone or combined with “obesity” or “knee osteoarthritis”. Due to the narrative nature of this review, selection bias cannot be excluded. Conclusions: Obesity is associated with osteoarthritis progression, as it increases joint pain and radiographic progression. Weight loss and physical exercise are effective treatment strategies in patients with osteoarthritis both treated surgically and non-surgically. Irisin shows anti-inflammatory effects in in vitro and in vivo studies, but in human it is rather a modulator or marker of exercise efficacy. IL-6 is a highly context-dependent cytokine that is generally considered pro-inflammatory but may also exert anti-inflammatory effects when acting as a myokine.